2022
DOI: 10.3390/healthcare10030545
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Primary Care Physicians towards COVID-19 in Greece: A Cross-Sectional Study

Abstract: The aim of this study was to investigate the knowledge, attitudes, and practices of primary care physicians and residents towards the COVID-19 pandemic in Greece. A cross-sectional questionnaire-based study was conducted in Greece during March 2021. The population frame for the study was a list of currently practicing primary care physicians and residents who were registered within one of the main associations of general/family medicine in Greece. Hierarchical multiple logistic regression analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
2
5
3
Order By: Relevance
“…While studies from Saudi Arabia, Sierra Leone, and Jordan also discovered that male healthcare workers, like the male GPs from Bosnia and Herzegovina in this study, had more positive attitudes toward COVID-19 prevention and control [15,32,38], another study from Saudi Arabia, and studies from India and China, contrary to the results among the Bosnian GPs in this study, showed that females had more positive attitudes than males [19,34,43]. Finally, a study that included GPs from the United States, Turkey, and Greece and another study that included only GPs from Greece found no connection between gender and attitudes toward COVID-19 prevention and control [7,29]. A study among frontline healthcare workers in India also discovered that healthcare workers with a longer length of service had more positive attitudes toward COVID-19 prevention and control [21].…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…While studies from Saudi Arabia, Sierra Leone, and Jordan also discovered that male healthcare workers, like the male GPs from Bosnia and Herzegovina in this study, had more positive attitudes toward COVID-19 prevention and control [15,32,38], another study from Saudi Arabia, and studies from India and China, contrary to the results among the Bosnian GPs in this study, showed that females had more positive attitudes than males [19,34,43]. Finally, a study that included GPs from the United States, Turkey, and Greece and another study that included only GPs from Greece found no connection between gender and attitudes toward COVID-19 prevention and control [7,29]. A study among frontline healthcare workers in India also discovered that healthcare workers with a longer length of service had more positive attitudes toward COVID-19 prevention and control [21].…”
Section: Discussioncontrasting
confidence: 90%
“…Namely, this study revealed that among the Croatian GPs there were no significant associations between the various sociodemographic and employment variables and the GPs attitudes, and the only factor that was significantly associated with more positive attitudes toward the COVID-19 prevention and control was whether the GPs had finished formal education on the prevention of infectious diseases and occupational safety. Studies from several different countries also did not find significant connections between sociodemographic and employment variables and the attitudes of healthcare workers [7,20,23,29,30,40,41]. Studies from Saudi Arabia, China, and Pakistan confirmed that the participation of healthcare workers in formal education on the prevention of infectious diseases and occupational safety contributed significantly to their positive attitudes toward COVID-19 prevention and control, and this was also proven in this study, both for the Croatian and Bosnian GPs [28,30,34,42].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…According to our findings, the rate of resident doctors who adhered to the COVID-19 vaccination programme is close to 100%; in fact, only 0.26% of them did not receive a vaccination. These results show a very high compliance rate of MRs towards compulsory vaccination even compared to studies performed in other states [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 47%